An unusual case of type IIIB endoleak after repeat thoracic endovascular aortic repair at acute-angled arch: A case of fabric tear by bare-metal stent. (June 2022) - Nemoto, Atsushi; Yoshitake, Akihiro; Shimizu, Hideyuki
We report a case of an unusual case of type IIIB endoleaks after repeat thoracic endovascular aortic repair that was not visualized on computed tomography, first diagnosed during open conversion surgery, and successfully treated. A 69-year-old man had undergone repeat thoracic endovascular aortic repair for an enlarged thoracic aortic aneurysm six months before. His repeat computed tomography showed an acutely enlarged aneurysm, which had expanded from 80 to 96 mm in diameter, without any endoleaks. A type IIIB endoleak resulted from a small tear in fabric caused by a bare-metal stent of the previous endograft. The tip of the bare-metal of smaller outer endograft had penetrated a fabric portion of the inner larger endograft. The aneurysmal sac pressure was 58/46 mmHg, compared with a systemic pressure of 79/35 mmHg. The endografts were explanted and replaced with a vascular graft.